SURGICAL TECHNIQUE, SHORT- AND LONG-TERM RESULTS OF THE HORSESHOE KIDNEY TRANSPLANTATION - Sh. R. Galeev (Вестник трансплантологии и искусственных органов)
The experience of horseshoe kidney transplant operations is significantly restricted. Transplant surgeons often refuse to use horseshoe kidney due to a number of serious abnormalities of vessels and upper urinary tract in these organs. However, the constant shortage of donor organs and an increase in patients on the waiting list for kidney transplantation make us reconsider our approach to the selection of donor organs. The aim of this work was to demonstrate our result of horseshoe kidney transplantation.